Validação da nomenclatura de diagnósticos, resultados e intervenções de Enfermagem para a clínica médica do Hospital Universitário Lauro Wanderley/UFPB - Moura, Rafaela de Melo Araújo (2019)
Introduction: In order to clarify and improve the specific concepts of Nursing, one should highlight the use of Nomenclatures, which serve as reference for the nursing care provided to the patient, without disregarding the clinical judgment of the nurse. In order to corroborate and improve terminologies used in nursing professional practice, validation studies should be carried out. In content validation, experts should evaluate the information content of each item with maximum clarity and representativeness in order to avoid distortions in the study. In the clinical validation, through clinical case studies, it is important to gather detailed information that allows representing the totality of a situation. Objective: To carry out the content and clinical validation of the Nomenclature of nursing diagnoses, outcomes and interventions for the Medical Clinic of HULW/UFPB. Method: This is a methodological study with a quantitative and qualitative approach. Results: The 97 concepts of nursing diagnoses/results of the Nomenclature for the Medical Clinic were mapped with the concepts of CIPE® Version 2017, obtaining 69 present concepts and 28 non-present concepts. Then, 37 nurses-specialists performed the content validation of the operational definitions of concepts of nursing diagnoses/outcomes, with 94 validated and three not validated. In the clinical validation stage, 20 case studies were performed with patients hospitalized in the HULW Medical Clinic, from September to December 2018. Ninety-five concepts of nursing diagnoses/outcomes and 438 concepts of nursing interventions were listed, with a mean of 4.6 interventions per concept of nursing diagnosis/outcome. Nursing diagnoses, outcomes and interventions were classified according to the Basic Human Needs of Horta, obtaining: Psychobiological Needs: 69 concepts of diagnoses/outcomes and 326 nursing interventions; Psychosocial needs: 23 concepts of diagnoses/outcomes and 100 nursing interventions; and Psychospiritual Needs: 3 concepts of diagnoses/outcomes and 12 nursing interventions. Conclusion: Content and clinical validation operationalize and improve the Nomenclature, updating its content and promoting the practice of the medical clinic as an enabling tool for the application of the nursing process and, especially, an instrument that values Nursing as a care science.